2019
DOI: 10.1177/0091415019837614
|View full text |Cite
|
Sign up to set email alerts
|

LGBT Older Adults at a Crossroads in Mainland China: The Intersections of Stigma, Cultural Values, and Structural Changes Within a Shifting Context

Abstract: In this article, we explore the lives of lesbian, gay, bisexual, and transgender (LGBT) older adults in mainland China, with an emphasis on the shifting nature of the cultural context. Based on a culturally informed perspective, the intersection of LGBT stigma with cultural values (familial responsibility, filial piety, and loss of face) and larger structural changes (the aftermath of the one-child policy, economic reforms and globalization, LGBT human rights, and HIV policies) are creating dramatic shifts in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 32 publications
(58 reference statements)
0
27
0
3
Order By: Relevance
“…Perceived discrimination was associated with cognitive impairment, and this association is mediated by depression, anxiety, and social isolation. 55,56 Additionally, although no primary data specific to older LGBT people with HIV were available, Hua and colleagues 57 reviewed the invisibility of LGBT older adults in mainland China from the perspective of stigma and the shifting nature of cultural values (familial responsibility, filial piety, and loss of face) and structural context (policy and economic reforms, globalisation, human rights, and HIV policies) with a sub-focus on HIV, and highlighted the added discrimination and potential economic insecurity faced by LGBT people with HIV. 57 In Europe, HIV-related stigma was described as the most important factor affecting the lives of older people with HIV in the UK.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Perceived discrimination was associated with cognitive impairment, and this association is mediated by depression, anxiety, and social isolation. 55,56 Additionally, although no primary data specific to older LGBT people with HIV were available, Hua and colleagues 57 reviewed the invisibility of LGBT older adults in mainland China from the perspective of stigma and the shifting nature of cultural values (familial responsibility, filial piety, and loss of face) and structural context (policy and economic reforms, globalisation, human rights, and HIV policies) with a sub-focus on HIV, and highlighted the added discrimination and potential economic insecurity faced by LGBT people with HIV. 57 In Europe, HIV-related stigma was described as the most important factor affecting the lives of older people with HIV in the UK.…”
Section: Figurementioning
confidence: 99%
“…55,56 Additionally, although no primary data specific to older LGBT people with HIV were available, Hua and colleagues 57 reviewed the invisibility of LGBT older adults in mainland China from the perspective of stigma and the shifting nature of cultural values (familial responsibility, filial piety, and loss of face) and structural context (policy and economic reforms, globalisation, human rights, and HIV policies) with a sub-focus on HIV, and highlighted the added discrimination and potential economic insecurity faced by LGBT people with HIV. 57 In Europe, HIV-related stigma was described as the most important factor affecting the lives of older people with HIV in the UK. 58 A study in Switzerland, in which most study participants had disclosed their HIV status to others, found that the perception of HIV-related discrimination decreased with increasing age.…”
Section: Figurementioning
confidence: 99%
“…Stigma and social pressures from family members to get married and have children to protect family reputation and lineage are strong (Feng et al, 2010). These pressures are thought to directly stem from family policies that have shaped contemporary Chinese society (Hua et al, 2019). For example, the one-child policy coupled with an increasing aging population may exacerbate homophobia and transphobia, as same-sex relationships or gender nonconformity are commonly thought to undermine Chinese families and society (Cheng, 2018).…”
Section: Challenges To Health and Well-beingmentioning
confidence: 99%
“…In China, the government takes a vague stance on lesbians, gays, bisexuals, transgender, and intersex (LGBTI). As one of the most populous countries around the world, China provides a significant base of the world's largest LGBTI community ( 1 , 2 ). Despite a huge number of LGBTI in China (an estimate of 50–70 million population according to the seventh national population census of China), both state and local governments have chosen to distance themselves from those social issues in relation to sexual orientation and gender identity, holding a neutral attitude ( 3 ).…”
Section: Introductionmentioning
confidence: 99%